Improving Community Capacity in Rapid Disaster Mapping: An Evaluation of Summer School - Dewayany Sutrisno; Peter Tian-Yuan Shih; Mazlan bin Hashim; RongJun Qin; Pramaditya Wicaksono; Rahman Syaifoel (Indonesian Journal of Geography, 2019)
Experiences with natural disasters have intensified recent efforts to enhance cooperation mechanisms among official disaster management institutions to community participation. These experiences reveal a need to enhance rapid mapping technical assistance to be developed and shared among young scientists through a summer school. However, the question arose of how effective this summer school to be used as a tool to increase scientists’ understanding and capacity. This study sought to evaluate the extent to which human resource capacity building can be effectively implemented. The methods used for this evaluation is through observations, questionnaires and a weighted scoring based on knowledge, skills and attitudes’ criteria. The results indicate a significant improvement in knowledge (94.56%), skills (82%) and attitudes (85.20%) among the participants. Even though there are still gaps in participants’ skills, the summer school was found to be an effective way to train the young scientists for rapid mapping.